Effect of transcutaneous posterior tibial nerve stimulation and repetitive transcranial magnetic stimulation on neurogenic overactive bladder symptoms in female patients with multiple sclerosis: The study protocol of a randomized controlled study - Atak Çakir, Pinar; Mutluay, Fatma; Hanoğlu, Lütfü; Güzelburç, Vahit (Frontiers in Neurology, 2022)
Introduction Neurogenic bladder is frequently seen in patients with multiple sclerosis (MS). Electrical stimulation methods (neuromodulation) can be used for patients that have persistent symptoms despite pharmacological treatment. This study aims to compare the effects of two different neuromodulation techniques used in the treatment of neurogenic bladder. Methods and analysis This is a single-center randomized controlled trial for MS patients with neurogenic bladder. Patients determined to be eligible according to the study criteria will be randomized into two treatment groups: the transcutaneous posterior tibial nerve stimulation (PTNS) and repetitive transcranial magnetic stimulation (rTMS) groups. Each group will include eight patients. The patients will be treated for a total of 10 sessions for two consecutive weeks. The pressure-flow study will be used to compare the initial and final urodynamic results as the primary outcome. All the participants will fill in a 3-day bladder diary before and after the treatments in each group. Patients will also be asked to complete specific questionnaires for incontinence and quality of life (QOL): Overactive Bladder Questionnaire-V8 score (OAB-V8), Incontinence Severity Index (ISI), Incontinence Quality of Life Scale score (I-QOL), International Incontinence Questionnaire (ICIQ-SF) score, and International Consultation on Incontinence Questionnaire-Female Lower Urinary Tract Symptoms (ICIQ-FLUTS) score) as the secondary outcomes. Ethics and dissemination An ethical approval number was obtained from the Non-Invasive Clinical Research Ethics Committee of Istanbul Medipol University (ethical approval number: 768). Support was received within the scope of the Istanbul Medipol University Scientific Research Project with project number 2020—2017. The result of this study will be published in a peer-reviewed journal. Trial registration NCT05312138.